Title: Build Process of Adaptation to the New Environment in the Boys and Girls who Go Abroad - Karina Devi Utami; Drs. Hj. Sri Widowati Herieningsih, MS (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Go abroad for the people in Indonesia is commonly done for a purpose. One of the causes is the education. When male students and female students decided to go abroad, a lot of things to deal with. They are experiencing cultural differences often become an obstacle that ultimately hinder them in the process of adaptation in the new environment. This study aims to determine how the process of building adaptations made by male and female students in the new environment with a culture different from his native residence. The method used is descriptive qualitative interpretive paradigm. This study uses a U-curve Theory of Adaptation, Communication Accommodation Theory and Uncertainty Reduction Theory as a research platform. Data collection techniques are depth interviews with six informants consisting of three male students and three female students informants who wander in Semarang. The results of this study indicate that: (1) Informants feel the cultural differences in language, speech, and habits which lead to the informant experiencing culture shock. (2) The biggest obstacle faced by the informant is language. In female students, another obstacle to be faced is the loneliness and the hassles of arranging for day-to-day while the barriers are not perceived by male students (3) In the adaptation of intercultural, informants faced with a situation of anxiety and uncertainty caused by differences in cultural background and lack of information held by the informant about the culture and customs in the new environment. (4) The difference in cultural background into a major cause of anxiety and uncertainty. In informants coming from Sumatra, Kalimantan and Jakarta speech with intonation hard or fast as commonly practiced in residence of origin actually become an obstacle when in Semarang predominantly spoke more slowly and softly (5) Informants do strategy in an effort to reduce anxiety and uncertainty among others with an active strategy, interactive strategy, and passive strategies. (6) All the informants accommodation in its communication in different ways. (7) There is a difference homesick phenomenon through which the male students and female students. At the male student informants felt homesick duration shorter than female student informant. (8) In the process of building adaptation, informants in a variety of ways in order to adjust and comfortable in new environments such as opening up, interaction, eliminate prejudice, stereotypes, ethnocentric, and encouragement through motivation. (9) The results of adaptation to the informer male students showed a level of comfort more than the adaptation of female student informants, for the student informant barriers they feel homesick slow to be tolerated. (10) The process of building adaptation informants showed diverse curve